Innovative infrastructure financing through value capture in Indonesia. (Asian Development Bank, 2021)
Indonesia needs significant additional infrastructure investment to sustain its economic growth. However, the COVID 19 pandemic has further limited the fiscal space of the government. The report studies how Indonesia existing policies and regulations can be used to build a value capture framework that ensures the maximization of the social, economic, and environmental value of infrastructure investments. The framework focuses on strategies to deliver infrastructure projects that create greater value and, at the same time, generate funding for up front investment.